Pengaruh Jumlah Penduduk dan Dana Perimbangan Terhadap Pertumbuhan Ekonomi Melalui Belanja Langsung Tahun 2009-2013 - Inten Suari, Desak Ayu Putu; Martini Dewii, Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
Economic growth is a matter of a country's economy in the long term. Achieved economic growth rates of a country is measured from the development of real national income is achieved in a country. The success of a country can be measured in enhancing the welfare of its citizens through economic growth. The purpose of this study was to analyze the effect of the population and fund balance on economic growth through direct spending districts / municipalities in the province of Bali. Based on the analysis found that the number of the population has a significant and negative effect on the direct spending. Fund balance has a significant influence and positive impact on direct spending. The population does not have a significant and negative effect on economic growth. The balancing fund does not have significant and positive effect on economic growth. Direct spending has a significant and positive effect on economic growth. The population and the balance funds have indirect influence on economic growth through direct expenditure shown by direct spending that an intervening variable.
Keywords: Population; Balanced Fund; Growth; Shopping Direct